2016
DOI: 10.1515/revneuro-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenesis following experimentally induced traumatic brain injury – a systematic review

Abstract: AbstractTraumatic brain injury (TBI) is a complex neurotrauma in civilian life and the battlefield with a broad spectrum of symptoms, long-term neuropsychological disability, as well as mortality worldwide. Posttraumatic epilepsy (PTE) is a common outcome of TBI with unknown mechanisms, followed by posttraumatic epileptogenesis. There are numerous rodent models of TBI available with varying pathomechanisms of head injury similar to human TBI, but there is no evidence for an ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 160 publications
0
9
0
1
Order By: Relevance
“…CBZ, carbamazepine; CLB, clobazam; CLZ, clonazepam; GBT, gabapentin; LAC, lacosamide; OXC, oxcarbazepine; VPA, valproate; ZNS, zonisamide in subjects with suspected focal epilepsy. [ 18 F]GE-179 PET may have future clinical utility in supporting a diagnosis of epilepsy or for helping to identify subjects at a higher risk of developing epilepsy after brain insults such as stroke [43][44][45][46][47] and traumatic brain injury, 44,48,49 where increased excitotoxicity and elevated NMDAR levels are known to play a role.…”
Section: Resultsmentioning
confidence: 99%
“…CBZ, carbamazepine; CLB, clobazam; CLZ, clonazepam; GBT, gabapentin; LAC, lacosamide; OXC, oxcarbazepine; VPA, valproate; ZNS, zonisamide in subjects with suspected focal epilepsy. [ 18 F]GE-179 PET may have future clinical utility in supporting a diagnosis of epilepsy or for helping to identify subjects at a higher risk of developing epilepsy after brain insults such as stroke [43][44][45][46][47] and traumatic brain injury, 44,48,49 where increased excitotoxicity and elevated NMDAR levels are known to play a role.…”
Section: Resultsmentioning
confidence: 99%
“…Lateral fluid percussion injury (LFPI) in rats is employed to model post-traumatic epilepsy (PTE). 1,2 Documenting PTE has been mainly relying on video and EEG. [3][4][5] A notable weakness of such approach is its binary nature: It assumes that LFPI is either epileptogenic or is largely inconsequential.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral fluid percussion injury (LFPI) in rats is employed to model post‐traumatic epilepsy (PTE) 1,2 . Documenting PTE has been mainly relying on video and EEG 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Different from other types of epilepsy, post-traumatic epilepsy with a more complicated etiology is induced by many pathobiological mechanisms in parallel. In order to clarify the extent and exact mechanisms of the astrocyte involved, various kinds of post-traumatic epilepsy-induced traumatic brain injury models have been tested, including controlled cortical impact and the fluid percussion injury models (20), impact-acceleration models (21), weight-drop models, ferric chloride models, and so on (22). Some researchers demonstrated that the loss of astrocyte homeostatic functions possibly contributes to post-traumatic epilepsy (21).…”
Section: Introductionmentioning
confidence: 99%